2014
DOI: 10.1111/ecca.12119
|View full text |Cite
|
Sign up to set email alerts
|

A Pareto‐improving Minimum Wage

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 34 publications
0
5
1
Order By: Relevance
“… This contrasts with a number of previous studies that are ‘informationally inconsistent’ (e.g. Guesnerie and Roberts ; Allen ; Marceau and Boadway ; Boadway and Cuff ; Blumkin and Danziger ; Danziger and Danziger ). These studies assume that information on individual wages can be used to enforce a minimum wage, but not to condition taxes and transfers on wages, since this would allow the government to reach first‐best.…”
contrasting
confidence: 93%
See 1 more Smart Citation
“… This contrasts with a number of previous studies that are ‘informationally inconsistent’ (e.g. Guesnerie and Roberts ; Allen ; Marceau and Boadway ; Boadway and Cuff ; Blumkin and Danziger ; Danziger and Danziger ). These studies assume that information on individual wages can be used to enforce a minimum wage, but not to condition taxes and transfers on wages, since this would allow the government to reach first‐best.…”
contrasting
confidence: 93%
“…Boadway and Cuff () consider the framework of Mirrlees () and find that a minimum wage is desirable if it can be combined with a policy that forces the unemployed to accept any job that they can find. Danziger and Danziger () find a useful role for the minimum wage if it can be combined with a policy that forces firms to hire a certain number of low‐skilled workers, even if their marginal productivity is below the minimum wage. Blumkin and Danziger () consider a case in which the government redistributes from ‘lazy’ to ‘hard‐working’ low‐skilled workers who earn the same wage rate, but vary in the number of hours that they work.…”
Section: Earlier Literaturementioning
confidence: 99%
“…Boadway and Cuff (2001) consider the framework of Mirrlees (1971) and find that a minimum wage is desirable if it can be combined with a policy that forces the unemployed to accept any job that they can find. Danziger and Danziger (2015) find a useful role for the minimum wage if it can be combined with a policy that forces firms to hire a certain number of low-skilled workers, even if their marginal productivity is below the minimum wage. Blumkin and Danziger (2018) consider a case in which the government redistributes from 'lazy' to 'hard-working' lowskilled workers who earn the same wage rate, but vary in the number of hours that they work.…”
Section: Earlier Literaturementioning
confidence: 99%
“…It has long been recognized that in a competitive economy with optimal nonlinear income taxation and variable working hours, a constant minimum wage cannot improve social welfare (Allen, 1987;Guesnerie and Roberts, 1987). Recently, however, Danziger and Danziger (2015) have shown that a graduated minimum wage (that ties the minimum wage a rm must pay to the rm's size) can provide a strict Pareto improvement even in the presence of an optimal nonlinear income tax. Essentially, the graduated minimum wage forces rms to pay low-productivity workers above their productivity and thereby slackens the high-productivity workers' incentive-compatibility constraint.…”
Section: Introductionmentioning
confidence: 99%